A survey of users' perception and use of ICT resources in Kenneth Dike Library, University of Ibadan, Nigeria (2008)
This study examined the perception and use of ICT resources in Kenneth Dike library by postgraduate students of the university of Ibadan .The survey research design was adopted and 208 postgraduate students participated in the study. Data collected were analyzed using SPSS and results revealed that the use of ICT facilities to support learning and research in Kenneth Dike Library by postgraduate students is low, irregular and ineffective as majority of users lack adequate ICT awareness training and support to use ICT facilities available in the library. The study suggested that it is essential that active steps be taken to ensure that those who can most benefit from higher education are not further marginalized as majority of the users cannot access, use and receive support for ICT enabled learning in the university. The study recommended that Nigerian academic libraries should operate the manual system alongside the computerized system in order not to sideline the majority of staff and students who cannot access the computer until conversion is completed and fully appreciated by all library users.